2012
DOI: 10.1103/physrevlett.109.137002
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Characterization of Josephson Junction Arrays: Implementing a Low Loss Superinductance

Abstract: We have measured the plasma resonances of an array of Josephson junctions in the regime E(J)>>E(C), up to the ninth harmonic by incorporating it as part of a resonator capacitively coupled to a coplanar waveguide. From the characteristics of the resonances, we infer the successful implementation of a superinductance, an electrical element with a nondissipative impedance greater than the resistance quantum [R(Q)=h/(2e)(2) is approximately equal to 6.5 kΩ] at microwave frequencies. Such an element is crucial for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
278
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(285 citation statements)
references
References 28 publications
7
278
0
Order By: Relevance
“…[18], the ground capacitance C a g we estimate here is about three times bigger. Since the calculations throughout the paper are based on the original estimate of [18], they could underestimate, e.g., the dispersive shifts and the decay rates by almost one order of magnitude; we will return to this point when estimating the dephasing rate in Sec. VIII.…”
Section: Broken P T Symmetry: An Examplementioning
confidence: 89%
See 2 more Smart Citations
“…[18], the ground capacitance C a g we estimate here is about three times bigger. Since the calculations throughout the paper are based on the original estimate of [18], they could underestimate, e.g., the dispersive shifts and the decay rates by almost one order of magnitude; we will return to this point when estimating the dephasing rate in Sec. VIII.…”
Section: Broken P T Symmetry: An Examplementioning
confidence: 89%
“…For example, in Ref. [18] an array of 80 junctions was placed in parallel to a (resonator) capacitor and the 9 lowest resonant frequencies were measured. The system is described by the Hamiltonian H in Eq.…”
Section: Broken P T Symmetry: An Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Moving to a λ/4 resonator makes the current architecture sufficient in terms of resonator impedance. The impedance could be further increased using a high kinetic inductance based resonator [42] or by using an array of Josephson junctions [43].…”
Section: Towards Higher Coupling In Transmon Systems: a Proposalmentioning
confidence: 99%
“…Recently it was demonstrated that chains in this regime can be used as so called superinductors which have a high frequency impedance much larger than the quantum resistance 19,20 . There have been several successful experiments of the observation of quantum phase-slips in chains with large Josephson energy 21,22 .…”
Section: Introductionmentioning
confidence: 99%